Out of the Abyss: Genome and Metagenome Mining Reveals Unexpected Environmental Distribution of Abyssomicins - Iglesias, Alba; Latorre-Pérez, Adriel; Stach, James E. M.; Porcar, Manuel; Pascual, Javier (Frontiers in Microbiology, 2020)
Natural products have traditionally been discovered through the screening of culturable microbial isolates from diverse environments. The sequencing revolution allowed the identification of dozens of biosynthetic gene clusters (BGCs) within single bacterial genomes, either from cultured or uncultured strains. However, we are still far from fully exploiting the microbial reservoir, as most of the species are non-model organisms with complex regulatory systems that can be recalcitrant to engineering approaches. Genomic and metagenomic data produced by laboratories worldwide covering the range of natural and artificial environments on Earth, are an invaluable source of raw information from which natural product biosynthesis can be accessed. In the present work, we describe the environmental distribution and evolution of the abyssomicin BGC through the analysis of publicly available genomic and metagenomic data. Our results demonstrate that the selection of a pathway-specific enzyme to direct genome mining is an excellent strategy; we identified 74 new Diels-Alderase homologs and unveiled a surprising prevalence of the abyssomicin BGC within terrestrial habitats, mainly soil and plant-associated. We also identified five complete and 12 partial new abyssomicin BGCs and 23 new potential abyssomicin BGCs. Our results strongly support the potential of genome and metagenome mining as a key preliminary tool to inform bioprospecting strategies aimed at the identification of new bioactive compounds such as -but not restricted to- abyssomicins.